Urinary triclosan concentrations and early outcomes of in vitro fertilization-embryo transfer. Issue 3 (March 2017) - Hua, Rui; Zhou, Yao; Wu, Biao; Huang, Zhongwei; Zhu, Yongtong; Song, Yali; Yu, Yanhong; Li, Hong; Quan, Song
Abstract : Triclosan (TCS) exists ubiquitously in the environment. Several in vitro and in vivo studies have demonstrated that TCS exerts endocrine disruptive effects on reproduction, but data from human populations are limited and conflicting. The objective of our study was to investigate whether high urinary TCS concentration is adversely associated with early reproductive outcomes in women undergoing in vitro fertilization-embryo transfer (IVF-ET). This prospective cohort study was conducted from September 2015 to June 2016, including 156 infertile women undergoing their first IVF-ET cycle. Two spot urine samples were collected prior to oocyte retrieval for TCS detection using solid-phase extraction (SPE) and liquid chromatography coupled with tandem mass spectrometry (LC–MS/MS). Linear regression model and binary logistic regression model were used to evaluate the association between urinary TCS concentrations and IVF outcomes. The intake of aquaculture food may have positive influences on urinary TCS concentrations. After adjustment for age, body mass index (BMI), baseline follicle-stimulating hormone (FSH), antral follicle count (AFC) and smoking status, a significant decrease of top quality embryo formation and implantation rate was observed in patients with urinary TCS concentration greater than or equal to the median level (0.045 μmol/mol Cr). We concluded that TCS exposure may exert negative effects during early stages of human reproduction.